Sall1 in renal stromal progenitors non-cell autonomously restricts the excessive expansion of nephron progenitors - Ohmori, Tomoko (Sci Rep, 2015)
The mammalian kidney develops from reciprocal interactions between the metanephric mesenchyme and ureteric bud, the former of which contains nephron progenitors. The third lineage, the stroma, fills up the interstitial space and is derived from distinct progenitors that express the transcription factor Foxd1. We showed previously that deletion of the nuclear factor Sall1 in nephron progenitors leads to their depletion in mice. However, Sall1 is expressed not only in nephron progenitors but also in stromal progenitors. Here we report that specific Sall1 deletion in stromal progenitors leads to aberrant expansion of nephron progenitors, which is in sharp contrast with a nephron progenitor-specific deletion. The mutant mice also exhibited cystic kidneys after birth and died before adulthood. We found that Decorin, which inhibits Bmp-mediated nephron differentiation, was upregulated in the mutant stroma. In contrast, the expression of Fat4, which restricts nephron progenitor expansion, was reduced mildly. Furthermore, the Sall1 protein binds to many stroma-related gene loci, including Decorin and Fat4. Thus, the expression of Sall1 in stromal progenitors restricts the excessive expansion of nephron progenitors in a non-cell autonomous manner, and Sall1-mediated regulation of Decorin and Fat4 might at least partially underlie the pathogenesis.